Graduate attributes, state policy, and Islamic preaching in Indonesia. - Millie, Julian (History & Anthropology, 2023)
The development of state institutions for the management and administration of Islam has enriched the range of Islamic authorities in Indonesia, with distinctive effects for public Islam. The article examines the effects of an Indonesian policy decision of 1975 that was intended to develop specific graduate attributes – 'modernity, openness and critical thought' – in graduates of Islamic post-graduate study. It was decreed that Islamic graduates would be sent to post-graduate programmes at universities in the West, altering a policy setting that had previously favoured venerable sites of Islamic learning in the Middle East. The Ministry of Religion associated sites of post-graduate learning in the West with graduate attributes of openness and critical thought, and perceived that these attributes were necessary for the development of a cohort of technical experts with competency to observe and analyse Islam in Indonesian populations. Article problematizes this notion of graduate attributes in the religious sphere, noting their novelty in comparison with competencies required of Islamic leaders in Indonesian communities (connectedness, affirmation of tradition, ritual expertise, etc). Attributes of 'openness and critical thought' position technical experts as critical observers of other segments in Indonesian Islamic society, such as Indonesia's popular preachers, many of whom are trained in sites of Islamic learning in the Middle East. In Indonesia's contemporary Islamic public sphere, such technical experts, many of whom were trained in Western social science departments, maintain a critical distance from Indonesia's popular preachers, the majority of whom (ironically) received religious training in sites of learning in the Middle East.